Business research methods and statistics using SPSS - Burns, Robert B.; Burns, Richard A. (Los Angeles ; London : SAGE, 2008)
Business Research Methods and Statistics Using SPSS provides a simple, easy to follow, and non-mathematical approach to understanding and using quantitative methods and statistics. It is solidly grounded in the context of business and management research, enabling students to appreciate the practical applications of the techniques and procedures explained. The book is comprehensive in its coverage, including discussion of the business context, statistical analysis of data, survey methods, and reporting and presenting research. A companion website also contains four extra chapters for the more advanced student, along with PowerPoint slides for instructors, and additional questions and exercises, all of which aim to help students to: * Understand the importance and application of statistics and quantitative methods in the field of business * Design effective research studies Interpret statistical results * Use statistical information meaningfully * Use SPSS confidently Ideal for those with a minimum of mathematical and statistical knowledge, this book will be an invaluable resource for students on quantitative methods courses in Business and Management, Organization Studies, Marketing Research and Economics.
GENERAL ORIENTATION TO RESEARCH IN BUSINESS AND MANAGEMENT -- ENTERING, DESCRIBING AND OBTAINING DATA -- STATISTICALLY ANALYSING DATA -- SURVEY METHODS FOR RESEARCH IN BUSINESS AND MANAGEMENT -- REPORTING AND PRESENTING RESEARCH
1
Keywords: SPSS (Computer file); Business -- Research -- Methodology; Business -- Research -- Statistical methods; Business -- Research -- Data processing